BOOSTING READING SKILLS THROUGH PLAY: BLOOKET’S ROLE IN TEACHING DESCRIPTIVE TEXT - Adelia Rizky Annisa; Emma Rosana Febriyanti; Eka Puteri Elyani; Raisa Fadilla (Premise: Journal of English Education and Applied Linguistics, 2025)
Descriptive text is an important part of the English curriculum in junior high school, especially for seventh-grade students. However, many students faced difficulties in understanding descriptive text, which hindered their reading comprehension and limited their academic achievement. Traditional teaching methods were often ineffective in engaging students. In contrast, gamification had been recognized as an innovative strategy to increase student motivation and improve learning outcomes. This study aims to determine the effect of the use of the Blooket platform on students' reading comprehension ability in descriptive texts. This study uses a quantitative method with a quasi-experimental design. The subjects of the study were 76 seventh grade students at SMPN 3 Banjarmasin who were divided into experimental classes and control classes through cluster random sampling techniques. Both classes are given pre-tests and post-tests that focus on descriptive texts. The data analysis technique used was the Mann-Whitney U test with the help of SPSS version 26. The result showed that there was a significant difference between the post-test scores of students taught using Blooket and those taught using Quizizz. The experimental class achieved higher scores, with a significance value 0.000, which was lower than the 0.05 threshold. It can therefore be concluded that the Blooket platform had a significant positive impact on students’ reading comprehension of descriptive texts. Consequently, it is recommended that English teachers integrate Blooket into their teaching practices to foster greater student engagement and improve comprehension outcomes.